Influência da composição dietética nas alterações cognitivas de idosos - Mecca, Marita Scarpim (Universidade Federal de São Carlos, 2011)
Currently the interest in investigating the role of nutrition and its influence on the development of cognitive functions has been increasing. This influence has been studied as a protective involvement and/or in retardation of dysfunctions and degenerative changes inherent to aging. The objective of this study was to assess the influence of diet composition on cognitive impairment of elderly people. Fifty individuals over 60 years of age were evaluated, treated at the Unidade de Saúde Escola da Universidade Federal de São Carlos, and divided in two groups: without cognitive impairment (GS) and with cognitive impairment (GC). To obtain general data, an anamnesis was applied. A food frequency questionnaire and the 24-hour recall method were also applied to assess the diet. With the obtained data the nutrients were calculated in the software NutWin 1.5. After that, weight and height were measured and the BMI of the survey participants was taken. For statistical analysis were done the tests chi-squared, t student, Wilcoxon Mann Whitney, Shapiro Wilk, a multiple correspondence analysis (MCA) , and the significance level was pre-set = 0,05. Individuals from group GS were predominantly classified as obese , and the ones from group GC as eutrophic . There was a significant difference between the groups, throughout life, regarding exercising more than three times a week, altered bowel movement, daily intake of fruits, vegetables, leafy vegetables, wholegrain products and sweet, and also an intake of nuts and fastfood three times a week. There was also difference regarding inadequacy of nutrients for VitA, B12, B6 and Zinc. We can observe with this research that healthy habits seem to be related to lower risks of cognitive impairment in old age, thus more Nutrition programs for the population are needed, aimed to the health promotion and prevention of diseases.
Influence of dietary composition on cognitive change in elderly people
Keywords: Nutrição; Idosos; Cognição; Consumo de alimentos; Elder; Cognition; Food intake; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL